La mujer y el trabajo en la Hispania prerromana y romana - Carmen Alfaro Giner (Mélanges de la Casa de Velázquez, 2010)
We know something of female labour in pre-Roman and Roman Hispania from only a scant number of indicators: writings of ancient authors; images wrought in sculpture, steles or ceramics and a likewise small number of funeral inscriptions, or on objects of everyday use associated with a specific kind of work. In the first case there are merely a few odd notes; in the second case, the actions that they depict do show us the day-to-day reality of female labour. Very few epigraphs survive compared to those of men. The idea that we can gain through all this information will never fully reflect the day-to-day reality of those women: a tremendous range of activity which although little valued was the mainstay of the family and social development among the peoples of the Iberian Peninsula.